Farmers' Knowledge And Adoption Level Of Vub In Tebing Kaning Village, Bengkulu Utara Regency - Robiyanto Robiyanto; Wawan Eka Putra; Shannora Yuliasari; Lina Ivanti; Yahumri Yahumri; Tri Wahyuni (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2022)
The purpose of the study is to determine the level of knowledge and adoption of farmers on the use of new high yielding varieties (VUB). The research location is in Tebing Kaning Village, North Bengkulu Regency in March 2021. The selection of locations and respondents purposively are farmers and extension workers totaling 58 people who take part in labor-intensive technical guidance. Data collection is done through surveys. The results showed that the level of knowledge of farmers before and after the study on the introduction of VUB increased by an average of 20.07% for each measurement variable and the adoption of VUB technology showed high adoption by 36 samples (92%), moderate adoption rate by 14 samples (7%) and low adoption rate as much as 2 samples (1%)